The Study of Metaphors, Metonymies and Phrasal Verbs in Gotthold Ephraim Lessing’s Works Nathan the Wise - Mamatova Anora Iminovna (International Journal on Integrated Education, 2022)
This article discusses the concept of metaphors, metonymies and phrasal verbs in Gotthold Ephraim Lessing’s works. According to our ancient ancestors, everything in this world is, to a certain extent, a word, and even the world itself is just a word. Gotthold Ephraim Lessing’s works of all periods work on the basis of a certain system of theoretical views in their field of translation. Like all events and phenomena in nature and society, a translation study has its own multifaceted object of study.